Policy Agenda for the Utilization of Space in the Penanggungan Cultural Heritage Area in Mojokerto Regency in the context of Protection of Cultural Heritage - Cik Ida Kumalasari Amirudin; Bambang Supriyono; Abdullah Said (Wacana Journal of Social and Humanity Studies, 2019)
This study aims to analyze the policy agenda of the utilization of the retaining cultural heritage area in Mojokerto Regency in order to protect cultural heritage. This research is based on several problems, is a Cultural Heritage that hasn’t been determined based on regulations, most of the Cultural Heritage located in the open air so that’s quickly damaged and weathered, location not strategic, and limited norms for preservation cultural heritage. So, the author conducted an analysis using a policy agenda model, by assessing a number of conflicts of interest from several stakeholders. The type of research used is descriptive and historical research with a qualitative approach. The results showed that the policy agenda of the utilization of cultural heritage area in Mojokerto Regency still had a number of conflicts of interest between the cultural observer, between the Regional Apparatus Organizations in the local government and the local community. The author gives recommendations to the government is to take into consideration and unite some of these interests, given the cultural interest in preserving cultural heritage in accordance with the Mandate of the Law and is an important aspect that must be implemented by the state in preserving historical heritage.